Food Allergy Perceptions and Health-Related Quality of Life in a Racially Diverse Sample - Alicia Toeruna Widge; Elizabeth Flory; Hemant Sharma; Linda Jones Herbert (MDPI AG, 2018)
This study examined caregiver perceptions of risk of food allergen exposure, and food allergy severity, worry, and health-related quality of life, and identified variations by race/ethnicity. Given the lack of data on racial/ethnic background in research on the psychosocial impacts of food allergy, this study meets a pressing need for research regarding food allergy-related experiences among diverse populations. This study found there were significant differences in perceived risk of allergen exposure among racial/ethnic groups with Asian Americans reporting significantly higher perceived risk of allergen exposure than Hispanic, Caucasian, and African American caregivers. There were no significant differences in food allergy severity, food allergy worry, or health-related quality of life among racial/ethnic groups; however, variability among racial/ethnic groups was apparent. Data may inform screening, counseling, and education practices for families from diverse backgrounds and aid in hypothesis generation for future research.